Intercultural communication in the light of current modernization process, "soft power" cultural modulators - A. V. Shestopal; M. V. Silantjeva (Vestnik MGIMO-Universiteta)
The problem of "soft power" is considered by the authors in the context of the linguistic-cultural, sociological, political and philosophical perspectives, providing a holistic view of today's complex process of intercultural interaction.